Implementation of Lean Concept in Healthcare Service Sector for Reducing Waste System: A Case Study of Radiotherapy Department Tertiary Hospital / การประยุกต์ใช้แนวคิดลีนกับภาคบริการทางการแพทย์เพื่อลดความสูญเปล่า ของระบบกรณีศึกษา แผนกรังสีรักษา โรงพยาบาลตติยภูมิ - อุไรวรรณ วรรณศิริ, Uraiwan Wanasiri / (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 3 (2016): September - December 2016, 2016)
บทคัดย่อ บทความวิจัยนี้นำเสนอการประยุกต์ใช้แนวคิดลีนกับภาคบริการทางการแพทย์ เพื่อลดความสูญเปล่าของระบบ กรณีศึกษา แผนกรังสีรักษา โรงพยาบาลตติยภูมิ เนื่องจากปัญหาการรอเข้ารับบริการทางการแพทย์มีระยะเวลานาน โดยมีวัตถุประสงค์เพื่อศึกษาระบบการปฏิบัติงานของภาคบริการทางการแพทย์ในแผนกรังสีรักษา เพื่อศึกษาการประยุกต์ใช้ระบบลีนกับภาคบริการทางการแพทย์ในแผนกรังสีรักษา และเพื่อศึกษาการลดความสูญเปล่าทั้งระบบของภาคบริการทางการแพทย์ในแผนกรังสีรักษา วิธีการศึกษาประกอบด้วยการเก็บรวบรวมข้อมูล การนำเครื่องมือของลีนมาวิเคราะห์ข้อมูล และออกแบบเพื่อแก้ปัญหาการลดความสูญเปล่าทั้งระบบ ผลการศึกษาพบว่าการให้บริการทางการแพทย์ของแผนกรังสีรักษา มีกระบวนการที่ซับซ้อนและใช้เวลานาน เมื่อได้ประยุกต์ใช้ระบบลีนเพื่อนำมาวิเคราะห์หาความสูญเปล่า พบว่าความสูญเปล่าเกิดขึ้นจากการรอคอยที่ไม่เกิดคุณค่า และการใช้พื้นที่ให้บริการของแผนกไม่เต็มประสิทธิภาพ หลังจากนั้นได้นำเครื่องมือลีนมาออกแบบการแก้ปัญหาให้เหมาะสมกับระบบการให้บริการทางการแพทย์ พบว่าสามารถลดขั้นตอนและเวลาการให้บริการทางการแพทย์ทั้ง 2 ประเภท คือ 1) ผู้ป่วยเก่า/ผู้ป่วยนัด จาก 3 ขั้นตอน เหลือ 2 ขั้นตอน  เดิมใช้เวลา 310 นาที ลดเหลือ 190 นาที 2) ผู้ป่วยใหม่/ไม่ตรงนัด จาก 8 ขั้นตอน เหลือ 6 ขั้นตอน เดิมใช้เวลา 770 นาที ลดเหลือ 530 นาที อีกทั้งยังสามารถให้บริการคนไข้ได้เพิ่มขึ้นจาก 24 คน เป็น 50 คนต่อวัน ส่งผลให้สามารถเพิ่มประสิทธิภาพภาคบริการทางการแพทย์ได้ดียิ่งขึ้น   คำสำคัญ : แนวคิดลีน ความสูญเปล่า โรงพยาบาลตติยภูมิ    Abstract This paper proposes Applying Lean Systems in Radiotherapy Department for Reducing Waste Systems Tertiary Hospital.  Due to long waiting problem in receiving healthcare service, the objectives were to study the performance of the Radiotherapy Department in healthcare services and implementation of a lean system with reduces the process waste. The study consisted of data collection, lean tools used for data analyze and applying solution designed for reducing waste throughout the system.  The study found that the Radiotherapy Department healthcare services had the complex processes and took long time. By analyzing the processes and identifying wastes, it found that wastes incurred by unnecessary waiting and inefficient uses of department service areas. After applying lean tools designed for resolving the problems and redesigning the healthcare service processes, it was found that the Radiotherapy Department could reduce the processing and times in two categories: 1) For current patients/appointment patients processes, reducing process steps from 3 steps to 1 step and reducing from 310 minutes to 190 minutes, 2) For new patients/missing appointment patients processes, reducing process steps from 8 steps to 6 steps and reducing time from 770 minutes to 530 minutes.  It also increased outpatient services from 24 people to 50 people per day, which led to increased efficiency in the Healthcare Service.   Keywords : Lean Concept, Waste, Tertiary Hospital
Keywords: แนวคิดลีน ความสูญเปล่า โรงพยาบาลตติยภูมิ Lean Concept, Waste, Tertiary Hospital